Eye Contact and Fear of Being Laughed at in a Gaze Discrimination Task - Torres-Marín, Jorge; Carretero-Dios, Hugo; Acosta, Alberto; Lupiáñez, Juan (Frontiers in Psychology, 2017)
Current approaches conceptualize gelotophobia as a personality trait characterized by a disproportionate fear of being laughed at by others. Consistently with this perspective, gelotophobes are also described as neurotic and introverted and as having a paranoid tendency to anticipate derision and mockery situations. Although research on gelotophobia has significantly progressed over the past two decades, no evidence exists concerning the potential effects of gelotophobia in reaction to eye contact. Previous research has pointed to difficulties in discriminating gaze direction as the basis of possible misinterpretations of others’ intentions or mental states. The aim of the present research was to examine whether gelotophobia predisposition modulates the effects of eye contact (i.e., gaze discrimination) when processing faces portraying several emotional expressions. In two different experiments, participants performed an experimental gaze discrimination task in which they responded, as quickly and accurately as possible, to the eyes’ directions on faces displaying either a happy, angry, fear, neutral, or sad emotional expression. In particular, we expected trait-gelotophobia to modulate the eye contact effect, showing specific group differences in the happiness condition. The results of Study 1 (N=40) indicated that gelotophobes made more errors than non-gelotophobes did in the gaze discrimination task. In contrast to our initial hypothesis, the happiness expression did not have any special role in the observed differences between individuals with high versus low trait-gelotophobia. In Study 2 (N=40) , we replicated the pattern of data concerning gaze discrimination ability, even after controlling for individuals’ scores on social anxiety. Furthermore, in our second experiment, we found that gelotophobes did not exhibit any problem with identifying others´ emotions, or a general incorrect attribution of affective features, such as valence, intensity, or arousal. Therefore, this bias in processing gaze might be related to the global processes of social cognition. Further research is needed to explore how eye contact relates to the fear of being laughed at.